The Effect Of Turmeric On The Quality Of Primary Dysmenorrhea Pain To Students - Kiswati (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: Dysmenorrhea is a painful felt in women when menstruation. The factor is the increase in prostaglandin in endometrium. Dysmenorrhea has differentiated become two primer dysmenorrhea and secondary dysmenorrhea. The incident rate of dysmenorrhea 64, 25% which are 54, 89% primer dysmenorrhea and 9, 36% secondary dysmenorrhea. From the interview result to 5 girls’ adolescent, 3 of them said that painful when they have menstruation every month. Many handlings use anti-inflamasi medications which have dangerous negative effect if used in the long term, such as skin rash and thrombocytopenia. Objective: To aim is to know the effect of giving traditional turmeric drink to pain quality of primer dysmenorrhea for girl teenager SMPN 7 Jember period 2017. Methods: quasi experiment (experiment semu) with research method used One Group Pretest Posttest Design. Approach model cross sectional with amount sample 50 adolescents who experience primer dysmenorrhea. The instrument in the research used painful scale Numeric Ratting Scale (NRS) data analysis used paired t-test / Wilcoxon Matched Pair Test. Results: They got the result p-value 0.000 < α (0.05) so, H0 has rejected the meaning is there is influence for giving traditional turmeric drink to pain quality of primer dysmenorrhea for girl teenager SMPN 7 Jember period 2017. Conclusion: Adolescents should be able to limit the use of the smartphone according to their needs and minimise smartphone use before going to bed at night. Turmeric can reduce painful quality dysmenorrhea.